Risk factors associated with complications of palliative drainage of ascites with tunneled peritoneal catheters - Machnik, Domenique; Fischer, Sarah; Vetter, Marcel; Lamprecht-Bailer, Ricarda; Rouse-Merkel, Rachel; Klett, Daniel; Neurath, Markus; Strobel, Deike; Zundler, Sebastian; Haberkamp, Sophie (Therapeutic Advances in Gastroenterology, 2025)
Background: Medically intractable ascites causes substantial distress in patients with palliative disease. Tunneled peritoneal catheters have been established as a feasible treatment option allowing patient-controlled paracentesis in a homecare setting. However, while a range of complications is associated with these drainages, risk factors for complications have not been identified so far. Objectives: To explore potential risk factors associated with complications of tunneled peritoneal catheters. Design: Retrospective observational cohort study. Methods: Single-center cohort comprising 49 patients with palliative disease receiving 57 tunneled peritoneal catheters at a tertiary care hospital. Results: Catheter placement was successful in all patients and associated with low numbers of severe complications. Our data suggest a higher risk for severe late complications in patients with benign disease, with drainage replacement, and when performed by less experienced physicians. Conclusion: Tunneled peritoneal catheters are an effective and safe option to treat symptomatic ascites in patients with end-stage palliative disease. The indication should be carefully considered in patients with benign disease and after removal or dislocation of a previous catheter.
CRIS-Team Scopus Importer:2025-01-31
Keywords: ascites; palliative care; peritoneal carcinomatosis; tunneled peritoneal catheter